Effectiveness of Digital Transformation in Data Warehouse Technology - Rohajawati, Siti (AI Society & STMIK Indonesia, 2024)
Banking performance must always be maintained in providing fast and accurate services based on data processing results. PT Bank ABC has several data warehouse from various sources. The technology used makes the reporting process more complex, and maintenance costs are high. This research presents the data warehouse system transformation process using a single source of truth approach and the use of Extract, Transform, and Load (ETL) tools from IBM InfoSphere DataStage version 11.5. ETL testing is carried out on the Performance Measurement System (PMS) process by business units to monitor, identify, and analyze performance in each business unit. The results obtained proved to be faster than DB2 and Oracle database queries. Using the DataStage platform provides advantages in time efficiency, which is a crucial factor in overall data processing. In addition, DataStage Integration can have a positive impact on overall system performance, support smooth operations, and minimize the potential for database server overload.